CdS Coated Mn Doped ZnO Nanospheres as Textile Catalyst: Fabrication, Physicochemical Techniques and Dye Removal Under Natural Light: Life Sciences-Environmental photocatalysis - Sivaranjani, K; Sivakumar, S; Dharmaraja, J (International Journal of Life Science and Pharma Research, 2022)
ZnO as a promising photocatalyst has gained much attention for the removal of organic pollutants from water. However, the main drawbacks of the relatively low photocatalytic activity and high recombination rate of photo excited electronhole pairs, restrict its potential applications. Promoting the spatial separation of photo excited charge carriers is of paramount signi? cance for photocatalysis, because the dierence in the band positions make the potential gradient at the composite boundary. In this work, our aim is to enhance the photocatalytic efficiency of CdS coated Mn doped ZnO nanospheres under solar light irradiation. Objectives in this work are, to fabricate the CdS coated Mn doped ZnO nanospheres by a simple ethanolic dispersion method, and its applied for testing the photocatalytic activity of methylene blue (MB) dye. The fabricated binary composites were analyzed with different physicochemical techniques like PXRD, SEM with EDX, UV-DRS, PL and TEM. The photocatalytic degradation results have revealed that, the CdS coated Mn doped ZnO nanospheres exhibits admirable activity toward the photocatalytic degradation of the MB. The remarkably enhanced photocatalytic activity of CdS coated Mn doped ZnO nanospheres can be interpreted in terms of lots of active sites, which efficiently separate the photo generated electron and holes. A plausible mechanism is also elucidated via active species trapping experiments with various scavengers, which indicating that the photo generated O2 -and. OH radicals play a crucial role in photo degradation reactions under visible light irradiation. This work suggests that, the rational design and construction of heterostructures is powerful for developing highly efficient, and reusable visible-light photocatalysts for environmental purification and energy conversion. The enhanced photo degradation activity indicates the potential of the nanocomposite for the treatment of organic pollutants from the textile wastewater.